Rotational Acetabular Osteotomy - Yasunaga, Yuji (JBJS Essent Surg Tech, 2017)
Hip dysplasia is a common cause of secondary osteoarthritis. To prevent the early onset of secondary osteoarthritis, rotational acetabular osteotomy has been proposed(1). DESCRIPTION: The approach combines the anterior iliofemoral and posterior approaches through a single skin incision. The pubic bone is cut independently, and the ilium and ischium are cut in continuity. The rotation of the acetabulum provides a more horizontal weight-bearing area and, at the same time, returns the superiorly subluxated femoral head to a more normal position. ALTERNATIVES: The Ganz periacetabular osteotomy involves the same concept as a rotational acetabular osteotomy with a different surgical approach. The rate of major complications, such as intra-articular osteotomy, nerve palsy, loss of fixation, malreduction, and symptomatic heterotopic ossification, is lower in rotational acetabular osteotomy (0% to 18%)(2) than in periacetabular osteotomy (6% to 37%)(3). Because of a wide surgical exposure, osteotomy can be performed under direct vision in rotational acetabular osteotomy. RATIONALE: Rotational acetabular osteotomy for osteoarthritis secondary to hip dysplasia can alter the position of the acetabulum en bloc and cover the femoral head with cartilage. For the unstable hip with dysplasia, the surgical procedure is needed for the prevention of osteoarthritis.